ظاهرة تغيير الديانة في الأرخبيل الماليزي: الخبرات النفسية والاجتماعية - Al Zuabi, L.; Mas'ad Saleh, M. A.; Bagotayan, S.; Amalina Ahmad Tajudin (Universiti Sains Islam Malaysia, 2024)
The main objective of this study is to explore the reasons why people leave their religion and convert to another religion or adopt another religious status. By using qualitative research analysis, the study explores the reasons why some people in Malaysian Peninsular have converted to Islam while others have embraced it. The study took into consideration whether the psychological, social and religious experiences of the converts affect their decision to convert. The data was collected through accurate interviews, both face-to-face and online, with converts to and from Islam. With purposive samples and a snowball, online interviews were conducted with apostates and face-to-face interviews with converts to Islam. The results of the data analysis showed that the phenomenon of religious conversion is a sensitive and complex issue in Malaysian Peninsular. The research found that the reasons for changing their previous religions or leaving the religion entirely vary greatly depending on the social, psychological and religious experiences of the converts. Thus, the reasons cited by most apostates about Islam seem more religious, but in fact more psychological and social. The reasons cited by those who converted to Islam are more social and psychological. For apostates, violence and contradiction in Quranic verses and Islamic education are the main reasons for abandoning Islam. Love, marriage, and material gain were among the reasons why some people converted to Islam. Therefore, the study concluded that the decision to leave the former religion is usually influenced by multiple, varied and interrelated reasons. Most of them were the result of social motives, which created psychological crises, and, in turn led to a change of religion.